2016
DOI: 10.1063/1.4960012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mid-gap defects and barrier interface reactions on tunneling behaviors of ZnO-i-Si heterojunctions

Abstract: Low-leakage pin diodes based on ZnO-i-Si are realized by redox reaction of aluminum with the native oxide SiOx into AlOx and by proper selection of annealing conditions. The main sources of electric leakage was found to arise from charge carrier tunneling via mid-gap states in the semiconductors or lowered tunneling barriers. Less mid-gap states in n-ZnO and high tunneling barrier of the i-layer are key to lowering the leakage. Proper post-annealing of pin diodes effectively heal the mid-gap defects, while mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Therefore, to harness full potential of the m-MoS 2 flake, a systematic study of its electrical properties is desired. Some recent reports mentioned anisotropic behaviour of layered TMDC and showed that MoS 2 exhibits highly anisotropic electronic and mechanical properties in comparison to isotropic crystalline materials such as Si and Ge [18,25,26]. For instance, dielectric constant in MoS 2 is highly direction dependent and profoundly depends on the number of layers present in the stack of the m-MoS 2 [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to harness full potential of the m-MoS 2 flake, a systematic study of its electrical properties is desired. Some recent reports mentioned anisotropic behaviour of layered TMDC and showed that MoS 2 exhibits highly anisotropic electronic and mechanical properties in comparison to isotropic crystalline materials such as Si and Ge [18,25,26]. For instance, dielectric constant in MoS 2 is highly direction dependent and profoundly depends on the number of layers present in the stack of the m-MoS 2 [27,28].…”
Section: Introductionmentioning
confidence: 99%